Proposed green marketing strategy to collaborate with tourism awareness group (Pokdarwis): Case study at Sein Farm, Bandung - Metriyana, Arni; Zaim, Ilma Aulia (Global Academy of Business Studies, 2024)
Purpose: This study aims to propose a development strategy using the Green Marketing Model to establish the Sein Farm as a sustainable tourism destination in collaboration with Pokdarwis (Tourism Awareness Group) Cisurupan, Bandung. Research Methodology: This study applied a qualitative method with thematic analysis. Data were collected through semi-structured interviews with respondents and unstructured focus group discussions (FGD) with Pokdarwis. The analysis was conducted using STP, PESTLE, SWOT & TOWS, Hexa Helix, and Sustainable Tourism Indicators. Results: Thematic analysis identified green marketing indicators, including eco-friendly products, affordable tour packages, natural resource use, certified human resources, and green attractions (tree planting and waste sorting) and farmer-style architecture. STP analysis positioned the Sein Farm for students, targeting urban schools interested in urban farming education. Pokdarwis collaboration supports sustainable tourism through cultural activities, waste management, traditional games, and community empowerment via eco-souvenirs and MSMEs. Conclusion: Integrating the Green Marketing Model with community collaboration enhances Sein Farm’s role as a sustainable tourism destination by merging environmental, educational, and cultural dimensions of sustainability. This approach positions the Sein Farm as a model for urban-farming-based ecotourism. Limitation: This study is limited to a qualitative approach with a specific case study at the Sein Farm Cisurupan, Bandung. Broader generalization may require quantitative validation and comparative studies of other sustainable tourism destinations. Contribution: This research enriches the sustainable tourism literature by presenting a practical framework that integrates green marketing with community collaboration, offering guidelines for developing eco-friendly tourism that preserves culture, protects the environment, and empowers communities through eco-products and MSMEs.